Design and development of a modified runway model of mouse drug self-administration - Pandy, Vijayapandi; Khan, Yasmin (Scientific reports, 2016)
The present study established a novel mouse model of a runway drug self-administration in our laboratory. The operant runway apparatus consisted of three long runways arranged in a zig-zag manner. The methodology consisted of six distinct phases: habituation, preconditioning, conditioning, post-conditioning, extinction and reinstatement. The effects of saline were compared with escalating doses of either ethanol (0.5–4.0 g/kg, i.p), heroin (5–40 mg/kg, i.p), or nicotine (0.1–0.5mg/kg, i.p) administered in the goal box during the conditioning phase (day 1 to day 5). A significant decrease in the time of trained (conditioned) mice to reach the goal box confirmed the subjects’ motivation to seek those drugs on day 6 (expression). The mice were then subjected to non-rewarded extinction trials for 5 days over which run times were significantly increased. After 5 days of abstinence, a priming dose of ethanol or heroin (1/5th of maximum dose used in conditioning) significantly reinstated the drug-seeking behavior. These results suggest that the modified runway model can serve as a powerful behavioral tool for the study of the behavioral and neurobiological bases of drug self-administration and, as such, is appropriate simple but powerful tool for investigating the drug-seeking behavior of laboratory mice.